Neonatal sepsis: A, B, C–don't ever forget herpes. (9th November 2011) - Fitzgerald, Lucy Anne; Kevitiyagala, Diluki; Gould, Steve; Zengeya, Stanley
Abstract : A 5-day-old male presents to the emergency department septic and jaundiced, is resuscitated and started on broad spectrum intravenous antibiotics. However tragically in this case despite showing initial signs of stabilisation, he deteriorated with refractory metabolic acidosis and disseminated intravascular coagulation, and later passed away. At postmortem, disseminated herpes simplex virus-1 (HSV-1) was found. Paediatricians are well aware of the risk factors for bacterial neonatal sepsis and actively seek information from parents to identify those children at risk. When however should a viral aetiology be considered? Should all neonates receive empirical therapy until proven otherwise? The authors review the literature surrounding neonatal HSV infection and discuss the potential pitfalls of empirical treatment.